Numerical Simulation of Glottal Flow in Interaction with Self Oscillating Vocal Folds: Comparison of Finite Element Approximation with a Simplified Model (Communications in Computational Physics, 2012)
In this paper the numerical method for solution of an aeroelastic model describing the interactions of air flow with vocal folds is described. The flow is modelledby the incompressible Navier-Stokes equations spatially discretized with the aid of thestabilized finite element method. The motion of the computational domain is treatedwith the aid of the Arbitrary Lagrangian Eulerian method. The structure dynamics isreplaced by a mechanically equivalent system with the two degrees of freedom governed by a system of ordinary differential equations and discretized in time with theaid of an implicit multistep method and strongly coupled with the flow model. Theinfluence of inlet/outlet boundary conditions is studied and the numerical analysis isperformed and compared to the related results from literature.